2018
DOI: 10.1111/jofo.12267
|View full text |Cite
|
Sign up to set email alerts
|

Breeding ecology of Kittlitz's Murrelets on Kodiak Island, Alaska

Abstract: Little is known about the breeding ecology of Kittlitz's Murrelets (Brachyramphus brevirostris), a species suspected to have experienced both local and regional population declines in recent years. We studied aspects of their breeding ecology on Kodiak Island, Alaska, to better understand this poorly described member of the family Alcidae. We found 53 nests of Kittlitz's Murrelets during our study (2008–2011) and placed nest cameras at 33 nests to collect data on parental nest attendance, nestling provisioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 72 publications
(101 reference statements)
0
11
0
Order By: Relevance
“…We placed still‐image, motion‐triggered cameras (Reconyx, Holmen, Wisconsin, USA; Primos, PC900 or PC90) 1‒3 m from active nests to monitor nest activity. Experiments showed that camera placement had no detectable effect on nest success (Lawonn et al 2018 b ), and cameras were set on every nest studied starting in 2011 (only every other nest before that). In 2011, three cameras were set to 1‐min intervals; out of 199 meal deliveries recorded, only one visit was shorter than 3 min, indicating a 3‐min interval was adequate to film >99% of visits by parents to the nest (Lawonn et al 2018b).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We placed still‐image, motion‐triggered cameras (Reconyx, Holmen, Wisconsin, USA; Primos, PC900 or PC90) 1‒3 m from active nests to monitor nest activity. Experiments showed that camera placement had no detectable effect on nest success (Lawonn et al 2018 b ), and cameras were set on every nest studied starting in 2011 (only every other nest before that). In 2011, three cameras were set to 1‐min intervals; out of 199 meal deliveries recorded, only one visit was shorter than 3 min, indicating a 3‐min interval was adequate to film >99% of visits by parents to the nest (Lawonn et al 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments showed that camera placement had no detectable effect on nest success (Lawonn et al 2018 b ), and cameras were set on every nest studied starting in 2011 (only every other nest before that). In 2011, three cameras were set to 1‐min intervals; out of 199 meal deliveries recorded, only one visit was shorter than 3 min, indicating a 3‐min interval was adequate to film >99% of visits by parents to the nest (Lawonn et al 2018b). Thereafter, all nest cameras were set to trigger after detecting animal motion (3 images at 1‐s intervals), as well as at standard 3‐min intervals from discovery of the nest to fledging.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations